SKUTKI PRAWNE ORZECZEŃ TRYBUNAŁU KONSTYTUCYJNEGO W UJĘCIU CZASOWYM - Trzaskowski, Roman (Zeszyty Prawnicze, 2017)
Effects of Constitutional Tribunal’s Judgments in the Time Perspective Summary The problem of the time effects of the Constitutional Tribunal’s rulings remain within the area of interest of both constitutional and civil law scholars. It is widely discussed because of its enormous practical importance: more and more often the common courts and the Supreme Court have to deal with the laws which have been declared unconstitutional. The main question is whether the courts should apply the unconstitutional law while deciding on a case in which legally significant events had taken place before the law was declared null and void. The Polish Constitution does not give a clear answer to this question. The most important provisions seem to be contradictory, which makes it possible to use them as arguments for opposing positions. The scholars’ opinions differ significantly: some of them, followed by the Supreme Court, accept the so-called „retrospective” effect (the unconstitutional law cannot by applied), the others, together with the Constitutional Tribunal, take the opposite view. A few try to find a compromise. The proposition presented in this paper is to be classified as belonging to the third group. Indeed it seems that there is a need for a flexible approach. The time effects of a ruling shall be expressly stated by the Constitutional Tribunal. When the Tribunal fails to do so, the common courts have to asses themselves the rulings’ effects, being guided, among other things, by the principles of the civil law. There are strong arguments that the Constitution seems to favor the retroactive effect, yet it is not decisive. There are certainly situations, where a prospecitve effect shall be accepted: ultimately it is a question of balancing different constitutional and civil law values.